Sudden and Unexpected Death During Sexual Activity, Due to a Glial Cyst of the Pineal Gland. (June 2018) - Barranco, Rosario; Lo Pinto, Sara; Cuccì, Maria; Caputo, Fiorella; Fossati, Francesca; Fraternali Orcioni, Giulio; Ventura, Francesco
Abstract : Abstract: Cysts of the pineal gland are benign lesions. Often asymptomatic, in the majority of cases they are discovered incidentally during brain magnetic resonance imaging or autopsy. Sporadically, however, they may cause such symptoms as chronic headache, loss of consciousness, corticospinal and sensory impairment, and, in some cases, even sudden death. A 45-year-old woman, in apparently good health, collapsed and died suddenly, after reaching orgasm while engaged in sexual intercourse. According to the circumstantial account of her relatives, the woman suffered from severe headaches, which were exacerbated by certain types of physical strain, such as sexual activity. Postmortem examination revealed no external injuries or internal diseases except for a cystic lesion of the pineal gland. Microscopically, the wall of the cyst consisted of a layer of glial tissue surrounded by an area of pineal elements. A complete forensic approach concluded that the cause of death was fatal cardiorespiratory failure resulting from midbrain compression due to a nonneoplastic pineal gland cyst, exacerbated by sexual activity. In this case, the intracranial pressure increase, secondary to Valsalva maneuver during climax, may further aggravate compression on the brainstem, thus concurring to determine the death.